Transoral Surgery versus Primary Chemoradiation for Advanced Stage Head and Neck Squamous Cell Carcinoma. (2nd September 2014) - Lo, Emily J.; Truelson, John M.; Myers, Larry L.; Nedzi, Lucien; Yordy, John; Hughes, Randall; Sumer, Baran D.
Abstract : Objectives: Compare functional and survival outcomes between patients with advanced stage head and neck squamous cell cancer (HNSCC) treated with primary transoral surgery versus primary chemotherapy and radiation. Methods: Retrospective case‐control trial at an academic tertiary referral center. We identified a surgical group (SG) comprised of 37 patients with previously untreated stage III and IV HNSCC who underwent either transoral robotic surgery (TORS) or transoral laser microsurgery (TLMS) and a nonsurgical group (NSG) of 75 patients treated with primary chemotherapy and radiation between July 2007 and November 2011. NSG was matched to SG by age, sex, tumor location, stage, tobacco and alcohol use, and ECOG status. Tracheostomy and percutaneous gastrostomy tube (PEG) rates during treatment and at follow‐up, as well as survival outcomes, were examined. Results: There were no statistically significant differences in the matched variables. Significantly fewer patients in the SG compared with the NSG still had PEG at follow‐up, 8% versus 25%, respectively ( P =. 031). All patients in the SG versus 92% of the NSG were eventually decannulated. Seventy‐eight percent of the SG required postoperative radiation. The SG received an average radiation dose of 6164 ± 340 cGY versus 6854 ± 264 cGy for the NSG ( P =. 001). Kaplan‐Meier analysis showed no significant difference in survival outcomes. Conclusions: Comparison between the primary transoral surgery and primary chemoradiation groups for treatment of advanced HNSCC demonstrates similar survival outcomes. Patients who undergo surgery receive significantly lower doses of radiation, and most are able to regain functional swallow and be successfully decannulated.